Primeiro registro documentado de Alectrurus tricolor para o Pantanal, Brasil - Cestari, César [UNESP] (My University, 2006)
The Cock-tailed Tyrant (Alectrurus tricolor, Vielliot 1816) is reported here for the first time in the Brazilian Pantanal. The species was seen twice (August and September 2005) in the northern portion of Fazenda Rio Negro, in the region of Nhecolândia. Sexual displays were observed, suggesting that reproduction is occuring in this area.
First documented record of Alectrurus tricolor in the Pantanal, Brazil
Keywords: Alectrurus tricolor; Brazil; Mato Grosso do Sul; Pantanal; display behavior; new record; passerine; reproduction; South America